Hand-product contact point detection on surgical instruments - a user evaluation - Sampaio, Álvaro M. (2019)
FEATURE AT A GLANCE: The interaction of hand tools with the user is crucial and a key factor for his or her performance. In specific medical devices like surgical instruments, it is also important to ensure patient safety, namely, to avoid the risk of a surgical instrument's being left inside a body.This article investigates the patterns of hand-to-product contact areas by identifying the potential locations to couple an external add-on tracing device on surgical instruments. A user evaluation study was conducted to determine the contact areas between the surgeons' hands and different surgical instruments. The methodology, the results, and a discussion are described below.